2009
DOI: 10.1093/bja/aen319
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal seal of the novel supralaryngeal airway device I-Gel™ in comparison with the laryngeal mask airways Classic™ and ProSeal™ using a cadaver model

Abstract: Both the pLMA and cLMA provided a better seal of the oesophagus than the novel I-Gel airway. The pLMA and I-Gel drain off gastrointestinal fluid fast through the oesophageal lumen. Thus, tracheal aspiration may be prevented with their use. Further study is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 21 publications
4
59
0
4
Order By: Relevance
“…A recent study comparing the i-gel TM to an endotracheal tube showed a comparable seal (in terms of leak fraction) -albeit under pressure controlled ventilation 19 . However, in another study using a cadaver model, the oesophageal seal pressure of the i-gel TM was found to be significantly lower than with the Classic TM and ProSeal TM laryngeal masks 20 . In initial investigations performed on cadavers it was found that the i-gel TM effectively mirrored the perilaryngeal anatomy and that it consistently achieved positioning for supraglottic ventilation 21 .…”
mentioning
confidence: 86%
“…A recent study comparing the i-gel TM to an endotracheal tube showed a comparable seal (in terms of leak fraction) -albeit under pressure controlled ventilation 19 . However, in another study using a cadaver model, the oesophageal seal pressure of the i-gel TM was found to be significantly lower than with the Classic TM and ProSeal TM laryngeal masks 20 . In initial investigations performed on cadavers it was found that the i-gel TM effectively mirrored the perilaryngeal anatomy and that it consistently achieved positioning for supraglottic ventilation 21 .…”
mentioning
confidence: 86%
“…This was shown in both cadaveric studies and in vivo studies. 22,24,25 While the PLMA and SLMA are seldom used electively for patients at risk of aspiration, the above studies suggest that the adequate seal provided will allow drainage of gastric fluid even at high intragastric pressure without increasing the risk of aspiration. This can be achieved when the airway devices are positioned correctly.…”
Section: Slma and Risk Of Aspirationmentioning
confidence: 99%
“…Numerous previous studies of these airway devices have demonstrated their easy, reliable insertion and low morbidity rate. (3)(4)(5)(6)(7) However, comparative studies involving all three aforementioned airway devices are lacking. One study testing the three devices used the laryngoscope-guided and gastric tubeguided methods of insertion, while another was conducted on paralysed, ventilated patients undergoing laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%